2022
DOI: 10.29333/ejgm/11550
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors Related to Fear of COVID-19 in the General Salvadoran Population

Abstract: The objective of this article is to determine the psychological factors which are associated with the fear toward COVID-19 as experienced by the Salvadoran population in general. Method:This study is exploratory, with a cross-sectional design. For data collection a digital survey in Google Forms was used. There was a non-probabilistic sample of 328 Salvadorans. The mean age in general was 27.90 years-old, with a standard deviation (SD) of 9.10; the mean age for men was 29.05 years-old (SD = 9.94), and the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the case of anxiety about COVID-19 and obsession about COVID-19, the finding is explanatory, as the death of a loved one can generate symptoms of anxiety and recurrent thoughts that, in turn, lead a person to experience a more prolonged mourning, even more so, when the death has been difficult, as when dealing with COVID-19 (Milman et al, 2020;Shear et al, 2012;Zisook et al, 1990). Given that anxiety is one of the most commonly identified disorders in the Salvadoran population (Chacón-Andrade et al, 2020;Gutiérrez-Quintanilla et al, 2020;Lobos-Rivera et al, 2022), the connection between pandemic grief and coronavirus anxiety makes sense. Regarding the relationships between pandemic grief and depressive symptoms, they can be explained due to the restrictions in social interaction that were present.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of anxiety about COVID-19 and obsession about COVID-19, the finding is explanatory, as the death of a loved one can generate symptoms of anxiety and recurrent thoughts that, in turn, lead a person to experience a more prolonged mourning, even more so, when the death has been difficult, as when dealing with COVID-19 (Milman et al, 2020;Shear et al, 2012;Zisook et al, 1990). Given that anxiety is one of the most commonly identified disorders in the Salvadoran population (Chacón-Andrade et al, 2020;Gutiérrez-Quintanilla et al, 2020;Lobos-Rivera et al, 2022), the connection between pandemic grief and coronavirus anxiety makes sense. Regarding the relationships between pandemic grief and depressive symptoms, they can be explained due to the restrictions in social interaction that were present.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the findings of the present study align with research addressing the variable of fear of COVID-19. For instance, a study in El Salvador reported that fear of COVID-19 moderately correlates with anxiety and slightly with depression in the adult population (Lobos-Rivera et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, more than 600 million cases of infection and six million deaths have been reported worldwide. Several repercussions of the pandemic and its subsequent isolation period have been observed around the world, including recurrent fear of death, fear of separation from family, tension, irritability, loss of appetite, fatigue, insomnia, nightmares, as well as symptoms of anxiety and depression, post‐traumatic stress disorder, and obsessive behaviors such as frequent hand washing and cleaning of objects of personal use (e.g., Anderson et al., 2020; Broche et al., 2021; Lobos et al., 2022; Mendoza et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These reactions to the COVID‐19 pandemic have been particularly tough for females; younger, single, or disabled people; health and essential workers; population having low levels of education, or only one child (compared with not having or having 2 or more), or living alone or in crowded households, or suffering from mental illness (Anderson et al., 2020; Broche et al., 2021; Lobos et al., 2022; Mendoza et al., 2020). On the other hand, several circumstances served as protective factors during the pandemic, including living in urban zones, living with parents, having some family financial stability, having a high‐income level, working outside home, and regularly chatting online with friends (Cao et al., 2020; Idowu et al., 2020; Sandín et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation